Kajian kebijakan pemerintah dalam pelayanan kesehatan lansia - Husna, Faizah Khotimatul; Syahputri, Rezyana Budi (Journal of Economics Research and Policy Studies, 2025)
A significant surge in the number of non-communicable disease cases also accompanies the rapid increase in the elderly population in Indonesia. Additionally, elderly individuals have a high risk of experiencing disabilities and losing independence due to non-communicable diseases. If left unaddressed, the dependency burden of the elderly will continue to rise, impacting the country's financial burden in funding healthcare issues. One way to address this issue is through policy interventions related to elderly healthcare services. This study aims to examine the government's efforts through its policies in implementing elderly healthcare services and to assess the adequacy of regulations, particularly in terms of elderly health education and information dissemination, curative efforts for the elderly, and the development of elderly healthcare service institutions. This research is designed as a documentation study, with data collection techniques using documentation. Data analysis is conducted through data reduction, content analysis, and conclusion drawing. The study concludes that regulations regarding elderly health education and information dissemination remain insufficient. Meanwhile, in terms of curative efforts for the elderly and the development of elderly healthcare institutions, the existing regulations are relatively adequate.